2022
DOI: 10.18408/ahuri7124801
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of residential tenancies and impact on investment

Abstract: This research examined policies and programs relevant to the housing pathways of ex-prisoners with complex support needs in NSW, Victoria and Tasmania, including what criminal justice costs and benefits result from current housing assistance settings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…While legislation differs between jurisdictions, each RTA generally covers rent increases, bonds, property maintenance and repairs, avenues for dispute resolution between tenants and landlords, and grounds for ending the tenancy. In recent years, several jurisdictions have reformed their RTAs, with changes in one jurisdiction often influencing others (Martin et al 2022a). Recent reforms include reducing no‐grounds eviction, increasing opportunities for tenants to have pets and make home modifications, and mandating minimum standards of housing conditions (Stone, Burke and Goodall 2022).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While legislation differs between jurisdictions, each RTA generally covers rent increases, bonds, property maintenance and repairs, avenues for dispute resolution between tenants and landlords, and grounds for ending the tenancy. In recent years, several jurisdictions have reformed their RTAs, with changes in one jurisdiction often influencing others (Martin et al 2022a). Recent reforms include reducing no‐grounds eviction, increasing opportunities for tenants to have pets and make home modifications, and mandating minimum standards of housing conditions (Stone, Burke and Goodall 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Their argument is that too many regulations, or regulations that ‘favour’ tenants, will lead to landlords selling their rental properties because it is too difficult and expensive to comply with the rules; this, in turn, will cause problems for renters because the number of available rentals will shrink further. This argument was evaluated and investigated through mixed methods in a report for the Australian Housing and Urban Research Institute (AHURI), co‐authored by us and Chris Martin, Milad Ghasri, Liss Ralston, Laura Crommelin, Sharon Parkinson and Eileen O'Brien Webb (see Martin et al 2022a). Our research found that, in case studies of Sydney and Melbourne, tenancy law is not a significant factor in landlords disinvesting from the rental market; landlords are most likely to disinvest because they wish to sell and realise capital gains, or obtain money for another investment (Martin et al 2022a, pp.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations